PENGARUH PENEMPATAN BENDUNG DI HILIR BELOKAN SUNGAI TERHADAP PEMBENTUKAN KONFIGURASI DASAR DAN SEDIMEN TERANGKUT - NEGARA, I DEWA GEDE JAYA; PUTRA, IDA BAGUS GIRI; YASA, I WAYAN; DEWI, KURNIA (GANEC SWARA, 2020)
Weir is one of the water buildings built across the river. Weirs are needed to elevate the river water level so that it meets the elevation of irrigation needs. In very diverse watershed conditions, it is very possible that a dam was built in a river channel that is not ideal because the river channel turns so that the building becomes less safe. To be able to know the safety of the weir from erosion that can cause the weir to collapse and break or overturn, it is necessary to conduct an experimental laboratory research on the position of the weir in the downstream of a river bend. Research related to its effect on sediment transport, especially in the formation of basic configurations needs to be known, because erosion at the bottom is the initial process of weakening the weir security. This research was conducted in the Hydraulics and Coastal Laboratory of FT. The irram in a river flume with a length of 8 m and a width of 50 cm. Weir test is carried out with 4 variations of discharge and 3 variations of the position of the weir downstream of the channel bends. Sedimentation data were analyzed by the methods of Mayer, Peter, Muler (M.P.M), Einstein and Shinohara-Tsubaki and topographic data analysis using the Surfer program. The results showed that in general the largest sediment transport occurred in the position of weir I at a distance of Â½ channel width downstream of the center of the channel bends for all tests, with the magnitude of sediment transport occurring from the MPM method Qs = 1x10-4 m3 / dt / m, Einstein Qs = 6,371x10-6 m3 / sec / m, and Shinohara-Tsubaki Qs = 1,7951x10-4 m3 / sec / m. More dominant scouring occurs at the foot of the weir downstream, with the basic configuration formed in the form of antidunes and standing waves, and based on the Froude (Fr) flow rate including subcritical flow (Lower Flow Regime) with the basic configuration form of ripples and dunes